2007
DOI: 10.1093/ps/86.6.1218
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic and Anaerobic Microbiology of the Immersion Chilling Procedure During Poultry Processing

Abstract: The development of treatments to reduce bacterial numbers on poultry carcasses is important for the overall hygienic quality of birds. The important washing effect of the immersion chilling procedure is discussed. Systematic monitoring of fecal bacterial indicators as well as some classic pathogens was performed at selected critical points in a water chiller ecosystem. Clostridium perfringens, fecal coliforms, Enterococcus sp., and Streptococcus sp. were found in all water chiller samples. The temperature of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The number of cells recovered varied between the different mixed microbial populations with the highest recovery from biofilms that included either E. faecalis and/or S. simulans. Other studies have shown similar results for the attachment of C. jejuni to E. faecalis and/or S. simulans biofilms (32,45,46). It has been suggested that these microorganisms that originate from poultry sources may provide a suitable environment for the survival and growth of C. jejuni in poultry processing plant environments (47,48).…”
Section: Jejuni In Mixed-species Biofilmsmentioning
confidence: 67%
“…The number of cells recovered varied between the different mixed microbial populations with the highest recovery from biofilms that included either E. faecalis and/or S. simulans. Other studies have shown similar results for the attachment of C. jejuni to E. faecalis and/or S. simulans biofilms (32,45,46). It has been suggested that these microorganisms that originate from poultry sources may provide a suitable environment for the survival and growth of C. jejuni in poultry processing plant environments (47,48).…”
Section: Jejuni In Mixed-species Biofilmsmentioning
confidence: 67%
“…While this limited the availability to statistically compare the data, the fact that this is the first microbiomic analysis of scalder and chiller processing tank waters speaks to the importance of this data. In order to initially investigate the microbiomes of the processing water tanks, the filtrate sampling method was used, considering it representative of a published processing tank sampling technique to remove organic particulates (Voidarou et al, 2007) and also to allow for a greater overall sample volume (∼100 mL) to be analyzed.…”
Section: Final Scalder and Chiller Water Tank Microbiome Changes Durimentioning
confidence: 99%
“…Therefore, studies assessing the efficacy of other disinfectants added in prechilling tanks may encourage Brazilian public health authorities to review the current legislation. According to Voidarou et al (2007), the pre-chilling step itself without any disinfectant has little effect on reducing microorganisms in broiler carcasses.…”
Section: Discussionmentioning
confidence: 99%